2017
DOI: 10.3390/molecules22050783
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexes of a New Family of Non-Ionic Amphiphilic Dendrocalix[4]arene and Poorly Water-Soluble Drugs Naproxen and Ibuprofen

Abstract: The inclusion complexes of a new family of nonionic amphiphilic calix[4]arenes with the anti-inflammatory hydrophobic drugs naproxen (NAP) and ibuprofen (IBP) were investigated. The effects of the alkyl chain’s length and the inner core of calix[4]arenes on the interaction of the two drugs with the calix[4]arenes were explored. The inclusion complexes of Amphiphiles 1a–c with NAP and IBP increased the solubility of these drugs in aqueous media. The interaction of 1a–c with the drugs in aqueous media was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Density functional theory calculations showed that the hydroxyl group on one side and the carboxyl group oxygen on the other side are the centers of the electron density localization and the hydrogen atoms are the most electropositive in its structure [ 35 ]. Calixarenes is one of the best examples of such carriers compounds that is enormously used in medicinal chemistry [ 34 , 36 , 37 , 38 , 39 , 40 ]. The synthesis of isosteviol based cages as a drug carrier needs to be explored as they are suitable carrier molecules.…”
Section: Chemistry Of Stevia Glycosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Density functional theory calculations showed that the hydroxyl group on one side and the carboxyl group oxygen on the other side are the centers of the electron density localization and the hydrogen atoms are the most electropositive in its structure [ 35 ]. Calixarenes is one of the best examples of such carriers compounds that is enormously used in medicinal chemistry [ 34 , 36 , 37 , 38 , 39 , 40 ]. The synthesis of isosteviol based cages as a drug carrier needs to be explored as they are suitable carrier molecules.…”
Section: Chemistry Of Stevia Glycosidesmentioning
confidence: 99%
“…The use of conjugation of two or more compounds has increased recently for potency and better solubility. They are either placed in a large carrier molecule through non-covalent interaction or through covalent conjugation of the known drugs to other biologically active compounds and cell-penetrating carrier compounds [ 39 , 40 ]. The same approach is used when conjugates of diterpenoid isosteviol and drug dimephosphon (1,1-dimethyl-3-oxobutylphosphonic acid dimethyl ester) are synthesized [ 129 , 130 ].…”
Section: Pharmacological Activities Of Isosteviol Derivativesmentioning
confidence: 99%
“…[73] This type of fluorescence spectra was observed in compounds containing naproxen moiety, which is also present in the ligand and complex 1. [74] Upon exciting the complex at 510 nm in buffer medium in the absence of ct-DNA, an emission band at 595 nm has been observed. With an increase in the concentration of the complex, the fluorescence intensity at 626-nm increases.…”
Section: Fluorescence Titration Methodsmentioning
confidence: 99%
“…Moreover, the synthesis of novel nonionic amphiphilic dendro-calix [4] arene compounds, which increased the solubility of hydrophobic drugs such as naproxen and ibuprofen, has been reported. Thus, it has been shown that the length of the alkyl chain and the intrinsic cyclic nature of the calixarene structure particularly affect the solubility of the drugs tested [ 39 ]. It is important to consider also that the solubility of the macrocycle, according to Lipinski’s rule of five, can increase the bioavailability of the drug [ 40 ].…”
Section: Calixarene: Structure and Applicationsmentioning
confidence: 99%